Incidence and Clearance of Anal Human Papillomavirus (HPV)-16 and HPV-18 Infection, and Their Determinants, Among Human Immunodeficiency Virus-Infected Men Who Have Sex With Men in France. (22nd November 2019) - Alberts, Catharina J; Heard, Isabelle; Canestri, Ana; Marchand, Lucie; Fléjou, Jean-François; Piroth, Lionel; Ferry, Tristan; Didelot, Jean-Michel; Siproudhis, Laurent; Henno, Sébastien; Poizot-Martin, Isabelle; Darragh, Teresa M; et al.
Abstract: Background: Prospective data on the natural history of anal human papillomavirus (HPV) infection are scarce in human immunodeficiency virus (HIV)-infected men who have sex with men (MSM). Methods: We analyzed incidence and clearance of HPV-16 and HPV-18 in a French cohort of HIV-infected MSM, aged ≥35 years, followed-up annually (n = 438, 2014–2018). Results: Human papillomavirus-16 and HPV-18 incidence were similar (~10% incident infections at 24 months). Human papillomavirus-16 incidence was higher among high-grade versus no lesion at baseline (adjusted incidence rate ratio = 3.0; 95% confidence interval, 1.07–8.18). Human papillomavirus-16 cleared significantly slower than HPV-18 (32% versus 54% by 24 months). Conclusions: In conclusion, anal HPV-16 is more persistent than HPV-18, and its incidence correlates with a prior detection of high-grade lesions. Abstract : We analyzed incidence and clearance of HPV-16 and HPV-18 in a French cohort of HIV-infected MSM. HPV-16 and HPV-18 incidence were similar, whereas HPV-16 clearance was slower than HPV-18. Finally, HPV-16 incidence correlated with a prior detection of high-grade lesions.